Evaluation of Nutritional Aspects of Maggot Flour (Hermetia Illucens L) As Feed Additive on Intestinal Villi Characteristics, Protein Digestibility, Energy Metabolism, and Nitrogen Retention in Broiler - Jihana, Amalia Iffah; Sjofjan, Osfar; Tistiana, Heli (Jurnal Nutrisi Ternak Tropis, 2024)
This study evaluated the nutrition of Maggot (Hermetia illucens L.) from various fruit waste media, food waste, tofu pulp, fruit rubbish + food waste, and tofu pulp + fruit waste. This study is divided into two stages: stage 1, which is carried out by proximate analysis and inhibitory testing of lactic acid bacteria (BAL), Escherichia coli, and Salmonella sp, and stage 2, which was an in vivo trial. Research material in stage 2 was DOC Strain Lohmann Platinum MB 202 as many as 160 tails are carried out in vivo trial method using a complete random design (CRD) consisting of five treatments and four replications where T0 (basal feed without treatment), T1 (basal feed + maggot flour 0.25%), T2 (basal feed + maggot flour 0.50%), T3 (basal feed + maggot flour 0.75%), T4 (basal feed + 1% maggot flour). The parameters measured were proximate, bacterial inhibitory power, intestinal villi characteristics, crude protein digestibility, Apparent Metabolizable Energy (AME), Apparent Metabolizable Energy Corrected Nitrogen (AMEn), and Nitrogen Retention in Broiler. Data was analyzed using the analysis of variety; if significantly different, results were then continued with the multiple distance test Duncan´s. The results showed that the use of tofu pulp + fruit waste produces maggots with the highest quality of nutrition and inhibition of bacteria, and the administration of maggot flour as feed additive of 0.50% shows the best results in increasing the characteristics of the intestinal villi broiler